Politeness Strategies In Disagreement Act Used By Students Of Eighth Grade In Smp N 1 Ngawen - Rahmaniar, Savira Yasmine, Agus Wijayanto, Ph.D, Dra. Siti Zuhriyah Ariatmi, M. Hum (2013)
The aim of this study is to describe type of politeness strategy in disagreement act used by the students of eighth grade in SMP N 1 Ngawen. This study uses descriptive kualitative method. The data are completing DCT text of disagreement act used by the students of eighth grade in SMP N 1 Ngawen. The data of politeness strategy were analized by Brown and Levinson. The research finding showed that there three type of politeness strategies. The students uses Positive Politeness, Negative Politeness and On-Record Politeness. The positive politeness that used by the students are attending to hearer, Using in group markers, Avoiding disagreement, Joking, Asserting speakers's knowledge of and concern for hearer's wants, offering/promising, including S and H in activity, Give (or ask for) reasoning, assuming or asserting reciprocity. The negative politeness that used by students are be direct and appologizing. As to gender, PP was mostly used by female in scenario 2, that is 14 responses, nevertheless PP was mostly used by male in scenario 2, that is 15 responses. Both of female and male mostly used PP 13. NP was mostly used both female in scenario 4, that is 8 responses and male in scenario 7, that is 6 responses. BOR was mostly used by female in scenario 6 and scenario 9, that is 4 responses , nevertheless BOR was mostly used by male in scenario 9, that is 5 responses. Based on findings, familiar relationship had a slight influence for respondents. The respondents used positive politeness mostly in E-C relationship, but respondents in H-U relationship used negative politeness more frequently. Bald on Record mostly used in L-U and the respondents was not used Off Record strategy.